First report of granulosa cell tumour associated with an endometrial adenoma in a crossbreed cow in Portugal - MOURA, D.; GARCÍA-DÍEZ, J.; SARAIVA, C.; PIRES, M. A. (Journal of the Hellenic Veterinary Medical Society, 2018)
A 12.5 year-old female crossbred cow without clinical signs at ante mortem inspection was slaughtered. The post-mortem inspection revealed poor carcass condition, interstitial nephritis and generalized lymphadenitis. The reproductive tract presented an unilateral and highly vascularized yellowish-white mass, with huge dimensions (60 x 40 cm and 20 Kg, approximately) described as granulosa cell tumour (GCT) and a endometrial adenoma, after histopathological analysis. GCT has been described as the most frequent ovarian tumour in cattle. Since clinical signs are usually unspecific, the post mortem diagnosis by histopathology examination is always necessary. The endometrial adenoma could be asymptomatic, with only absence of calving, or associated with GCT. This is, of our knowledge, the first report of a GCT associated with endometrial adenoma in a cow in Portugal.